2021
DOI: 10.2147/copd.s290363
|View full text |Cite
|
Sign up to set email alerts
|

Neurological and Psychiatric Comorbidities in Chronic Obstructive Pulmonary Disease

Abstract: Background and Purpose Chronic obstructive pulmonary disease (COPD) is often accompanied by different neurological and psychiatric comorbidities. The purpose of this study was to examine which of them are the most frequent and to explore whether their manifestation can be explained by underlying latent variables. Methods Data about patients with COPD and their neurological and psychiatric comorbidities were extracted from an electronic database of the National Health In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Epidemiological studies have identified a strong association between COPD and comorbid psychiatric disorders, including anxiety and depression, with the prevalence of depression ranging from 16% to 88.4%. In addition, individuals with COPD have a higher prevalence of ischemic stroke, transient ischemic attack, sleep disorders, dementia, and Parkinson’s disease, increasing with age [ 22 , 52 , 53 , 54 ]. There was no statistically significant difference in the diseased Lithuanian population in the prevalence of depression, but COPD patients were more likely to develop depression.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have identified a strong association between COPD and comorbid psychiatric disorders, including anxiety and depression, with the prevalence of depression ranging from 16% to 88.4%. In addition, individuals with COPD have a higher prevalence of ischemic stroke, transient ischemic attack, sleep disorders, dementia, and Parkinson’s disease, increasing with age [ 22 , 52 , 53 , 54 ]. There was no statistically significant difference in the diseased Lithuanian population in the prevalence of depression, but COPD patients were more likely to develop depression.…”
Section: Discussionmentioning
confidence: 99%
“…The unmet needs of COPD patients can hinder their effective disease management (Clari et al 2018, Chen et al 2019, Puteikis et al 2021. During the coping process with the nature of the disease, negative emotions such as feelings of loss, anger, fear of death, anxiety, depression, and hopelessness are commonly experienced (Clari et al 2018, Rehman et al 2021, Puteikis et al 2021.…”
Section: Psychological Issuesmentioning
confidence: 99%
“…Mental health and addiction concerns affect a large number of people around the world and are associated with various comorbidities including infections associated with healthcare or community source infection (Baroiu et al, 2019;Pumar et al, 2014;Puteikis et al, 2021).…”
Section: Major Comorbidities Of Copdmentioning
confidence: 99%